DIPG-60. Avapritinib for targeting PDGFRA in H3K27M – mutated diffuse midline glioma. (3rd June 2022) - Mayr, Lisa; Madlener, Sibylle; Weiler-Wichtl, Liesa; Rosenmayr, Verena; Furtner-Srajer, Julia; Guntner, Armin; Stepien, Natalia; Baumgartner, Alicia-Christina; Dorfer, Christian; Haberler, Christine; Müllauer, Leonhard; Palova, Hana; et al.
Abstract: H3K27M-mutated diffuse midline glioma (H3K27M DMG) are an almost universally fatal disease with a median survival of less than 6 months post progression and no effective therapy. PDGFRA-signaling has shown to promote and sustain a subset of oligodendrocyte precursor-like tumor cells that are responsible for tumor propagating potential and high proliferation rates. However, first attempts to target PDGFRA in adult glioblastoma with dasatinib/imatinib or pediatric refractory brain tumors with sunitinib were not successful. We report on the first experience in two patients receiving avapritinib, a highly potent, selective, brain penetrant PDGFRA/KIT inhibitor under a compassionate use program. Our first patient with spinal H3K27M DMG developed supratentorial metastases ten months after initial diagnosis. Molecular profiling revealed de novo PDGFRA and KIT amplifications and treatment with dasatinib was initiated. Due to disease progression and novel metastases, therapy was switched to avapritinib showing near complete resolution of the previously unirradiated frontal lesion with additional disease stabilization of other metastatic sites. Following re-resection and irradiation of progressing cerebellar lesions, the patient remains clinically stable on avapritinib therapy over 12 months. The second patient with diffuse intrinsic pontine glioma showed disease progression nine months after diagnosis and was treated with focal re-irradiation (30Gy). As the tumor harbored a PDGFRA R841del alteration, avapritinib was initiated seven weeks after radiation upon further tumor progression resulting in partial response. Pharmacokinetic sampling of cerebrospinal fluid (CSF) detected an increasing CSF/plasma ratio over time and up to 4 µM avapritinib in tumor tissue. Avapritinib CSF levels in both patients were distinctly higher than dasatinib levels. Avapritinib was generally well tolerated besides lower limb edema, elevated LDH and liver enzymes. Hence, effective CNS penetration of avapritinib at pharmacologically relevant brain tumor concentrations resulted in clinical response in two patients with rapidly progressive H3K27M DMG.